2017
DOI: 10.1007/s10865-017-9882-7
|View full text |Cite
|
Sign up to set email alerts
|

Racial (vs. self) affirmation as a protective mechanism against the effects of racial exclusion on negative affect and substance use vulnerability among black young adults

Abstract: Affirming one's racial identity may help protect against the harmful effects of racial exclusion on substance use cognitions. This study examined whether racial versus self-affirmation (vs. no affirmation) buffers against the effects of racial exclusion on substance use willingness and substance use word associations in Black young adults. It also examined anger as a potential mediator of these effects. After being included, or racially excluded by White peers, participants were assigned to a writing task: sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 78 publications
2
12
0
Order By: Relevance
“…However, only the anger and not the depression / anxiety mediated the discrimination → drug willingness relation in that group. Similar results were reported in another experimental study by Stock et al (2017) with a different sample. Collectively, these studies suggest that different affective responses to the stress produced by discrimination may be associated with different health-relevant outcomes.…”
Section: Emotional Responses As Mediatorssupporting
confidence: 92%
See 1 more Smart Citation
“…However, only the anger and not the depression / anxiety mediated the discrimination → drug willingness relation in that group. Similar results were reported in another experimental study by Stock et al (2017) with a different sample. Collectively, these studies suggest that different affective responses to the stress produced by discrimination may be associated with different health-relevant outcomes.…”
Section: Emotional Responses As Mediatorssupporting
confidence: 92%
“…Regarding the former, a study of Black parents and their children (part of the Family and Community Health Study [FACHS]) found that self-reports of discrimination were related to increases in anxiety and depression for both the parents and their children (Gibbons, Gerrard, Wills, Cleveland & Brody, 2004; see also Brown et al, 2000; Klonoff, Landrine, & Ulman, 1999). This relation has also been found in a recent experimental study showing that young Black adults who were excluded by Whites in an online game of Cyberball attributed that exclusion to racial discrimination and reported increases in depression (Stock et al, 2017). Importantly, internalizing affective responses have consistently been associated with decreases in health status, including chronic illnesses, physical limitations, poor immune functioning (Dickerson & Kemeny, 2004; Robles, Glaser, & Kiecolt-Glaser, 2005), as well as risk for STIs (Roberts et al, 2012).…”
Section: Emotional Responses As Mediatorssupporting
confidence: 72%
“…Sometimes this is through seeking out alternative avenues for acceptance and other times it involves simply affirming one's sense of identity or important values (Smart Richman & Leary, 2009). Indeed, recent research demonstrates that Black participants who were excluded because of their race recovered more quickly if they had the opportunity to affirm their identity as Black; interestingly, they did not receive the same recovery boost with affirming other aspects of their self-concept (Stock et al, 2018). That has interesting implications for microaggressions.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effectiveness of self-affirmation can depend upon the source of the exclusion. One study (Stock et al, 2018) examined race-based exclusion, finding that Black participants who were excluded by White computer-controlled players in an online game showed increased vulnerability to substance use, but this effect was mitigated when they could affirm their racial identity. A general self-affirmation task did not have the same protective effect, unfortunately.…”
Section: Discussionmentioning
confidence: 99%